PENERAPAN MODEL PEMBELAJARAN TAKE AND GIVE DALAM MENINGKATKAN HASIL BELAJAR IPA - Adnan K; Rukayah Rukayah; Sudarto, Sudarto; Nur Syahrina (Bajang Institute, 2024)
This research is a classroom action research that aimed to see the desciptions of the increasing of the number of the Fifth Grade students at SD Inpres 5/81 Tibojong whose his or her science learning outcomes have achieved completeness and incompleteness through the implementation of the Take and Give learning model. The subjects of this research were 20 fifth grade students. The action design in this research consists of two cycles with four stages, namely planning, implementation, observation and reflection. The data collection technique used is a test technique at the end of each cycle. The data analysis technique used is percentage descriptive statistical techniques. The research results showed an increase in the number of students who achieved complete science learning outcomes from 70% complete and 30% incomplete in cycle I to 90% complete and 10% incomplete in cycle II. Conclusion: the application of the Take and Give learning model can increase the number of class V students at SD Inpres 5/81 Tibojong, East Tanete Riattang District, Bone Regency whose science learning outcomes reach completion, which also means that the application of the Take and Give learning model can improve students' science learning outcomes